Effects of a computerized psychological inoculation intervention on condom use tendencies in sub Saharan and Caucasian students: two feasibility trials. Issue 1 (1st January 2019) - Levy, Einav; Gidron, Yori; Deschepper, Reginald; Olley, Benjamin O; Ponnet, Koen
ABSTRACT: Objective: An effective method for preventing the Human Immunodeficiency Virus (HIV) is condom use. Yet, research shows limited effects of education on increasing condom use. This research examined the effects of psychological inoculation (PI) versus education on condom use -barriers and –tendencies, using a fully automatized online system. Design: Two randomized controlled trials. In Study 1, 59 Sub-Saharan students were included while Study 2 20 European students were included. In both studies, participants were randomly assigned to PI or control conditions. In Study 2, we additionally matched pairs on gender and condom barriers. In the PI, participants received challenging sentences they had to refute. Main outcome measures: An indirect condom use test (I-CUTE) and a condom use barriers questionnaire, assessed at baseline and a month later. Results: In Study 1, a significant increase in I-CUTE scores and no change in barriers was found in the PI condition. Controls did not change on either outcome. In Study 2, two sub-scales of condom barriers (concerning partner and satisfaction) were significantly decreased in the PI group, while in controls, barriers significantly increased over time. In both groups, I-CUTE scores tended to increase. Conclusions: These results replicate previous studies and extend them to a fully automatized system without counselors.